2021
DOI: 10.1097/nna.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Staff Nurses' Perceptions of Nurse Manager Caring Behaviors and Patient Experience

Abstract: OBJECTIVE The objective of this study was to explore the relationship between staff nurses' perceptions of nurse manager caring behaviors and patient experience. BACKGROUND Despite numerous interventions aimed at changing the provision of patient care to improve care quality, patient experience scores have remained moderate. Little research has been conducted exploring how caring relationships in the professional practice environment might play a role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…And leaders' caring has been linked to organisational commitment, anxiety reduction at work, increased workplace selfesteem and, more tentatively, organisational performance and productivity (Kostich et al, 2020;Olender, 2017;Tomkins & Simpson, 2015). Furthermore, previous empirical studies have revealed that nursing leaders' caring behaviour positively influences staff nurses and patients (Kostich, 2020;Salinas et al, 2020), indicating the importance of caring leadership in clinical practice.…”
mentioning
confidence: 97%
“…And leaders' caring has been linked to organisational commitment, anxiety reduction at work, increased workplace selfesteem and, more tentatively, organisational performance and productivity (Kostich et al, 2020;Olender, 2017;Tomkins & Simpson, 2015). Furthermore, previous empirical studies have revealed that nursing leaders' caring behaviour positively influences staff nurses and patients (Kostich, 2020;Salinas et al, 2020), indicating the importance of caring leadership in clinical practice.…”
mentioning
confidence: 97%
“…Patient experience goes beyond the clinical outcomes or health conditions expected by the patient and is essential for providing patient‐ and family‐centred treatment (Hudon et al, 2012). Patient experience, which will continue to grow in importance in the future, consists of a variety of interactions with medical professionals and healthcare employees during a patient's stay in the hospital, among which a nurse's role is essential (Hessels et al, 2015; Kostich et al, 2021). Therefore, in addition to previous satisfaction surveys of patients, it is necessary to ascertain areas where healthcare experts can focus on enhancing competency and improving patient satisfaction, as in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nurse manager actions are necessary for creating and sustaining a healthy professional practice environment through balancing the tension between production efficiency and reliability. Successful nurse managing results in achieving safety; creating and sustaining trust throughout the workplace; managing the process of change; involving workers in decision‐making about work design and flow; and using knowledge management to establish the organization as a learning organization (Hersey & Blanchard, 1988; Institute of Medicine, 2004; Kostich, 2020). These elements of managerial actions are integrated with the caring behaviour of nurse managers.…”
Section: Introductionmentioning
confidence: 99%